2017
DOI: 10.1016/j.radcr.2017.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Incidentally discovered well-differentiated retroperitoneal liposarcoma with inguinal canal herniation: report of 2 cases

Abstract: Well-differentiated retroperitoneal liposarcomas are slow growing and low-grade tumors, reaching usually huge size before being symptomatic and so diagnosed, therefore with increase of the surgical risk and of the probability of dedifferentiation. Inguinal location of these tumors is unusual and rarely diagnosed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…[5] When the nonlipomatous areas exceed>2cm, it suggests the possibility of dedifferentiation. [4] The documented mean size of the DDLs is 17.5cm while here the tumor was a giant liposarcoma. [3] To the best of our knowledge, only 19 cases of giant retroperitoneal liposarcomas were documented in English literature until only eight were dedifferentiated.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…[5] When the nonlipomatous areas exceed>2cm, it suggests the possibility of dedifferentiation. [4] The documented mean size of the DDLs is 17.5cm while here the tumor was a giant liposarcoma. [3] To the best of our knowledge, only 19 cases of giant retroperitoneal liposarcomas were documented in English literature until only eight were dedifferentiated.…”
Section: Introductionmentioning
confidence: 78%
“…As is seen in the present case, rare instances have been documented in literature wherein inguinal hernia is their inaugural presentation. [4] The presence of fat components in radiology imaging findings can be helpful in the diagnosis of liposarcoma. [5] When the nonlipomatous areas exceed>2cm, it suggests the possibility of dedifferentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Although the underlying risk factors are not fully understood, multiple studies have suggested a probable connection to certain chromosal abnormalities. Liposarcomas can occur anywhere in the body [ 6 ]. The American Cancer Society lists a number of factors that can increase your risk of developing liposarcoma, including prior radiation, specific familial cancer syndromes, trauma to the lymphatic system, and exposure to hazardous chemicals.…”
Section: Discussionmentioning
confidence: 99%
“…Well-differentiated retroperitoneal liposarcomas are slow-growing, low-grade tumors that frequently reach large size before exhibiting symptoms and being found, raising the risk of surgery and the possibility of dedifferentiation [ 6 ]. It can be difficult to identify lipomas from WDLPS prior to surgery because both have a lot of fat and little soft tissue and look identical, despite the fact that imaging modalities, in particular CT-scan and MRI, are crucial to make a diagnosis in retroperitoneal tumors [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…26 Well-differentiated liposarcoma is the most common type in people and animals, 15,26 and is slow-growing and locally aggressive with uncommon recurrence after complete surgical excision. 12 In humans, approximately 10% of well-differentiated lesions dedifferentiate into nonlipogenic sarcomas with a 15% to 20% chance of metastasis. 9,13 Dedifferentiated liposarcoma most commonly arises in the retroperitoneum.…”
mentioning
confidence: 99%